PENERAPAN INOVASI E-PENDAPATAN PADA PAJAK PBB-P2 DI BADAN PENDAPATAN DAERAH (BAPENDA) KABUPATEN KUANTAN SINGINGI - Yulmaidah "; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The application of e-income innovation on PBB-P2 taxes at the Regional Revenue Agency (BAPENDA) of Kuantan Singing Regency is one of the steps taken by the Kuantan Singing Regency government in increasing regional income from PBB-P2 taxes. The application of e-income innovation is an innovation method in paying taxes using online payment methods. Where taxpayers only need to use Android from home and deposit through the Riau Islands Bank and other electronic payment media. However, this application brings several phenomena that can be seen by researchers, namely the lack of socialization carried out by the Bapenda in an effort to implement it so that not many people know about this e-income innovation. In addition, the realization of PBB-P2 tax revenue after the implementation of e-income innovation has not yet reached the target that has been set so that researchers are interested in researching how the process of establishing e-income innovation on PBB-P2 tax in the Regional Revenue Agency (BAPENDA) of Kuantan Singingi Regency as well as knowing what factors are the obstacles in the process of establishing e-income innovation on PBB-P2 taxes at the Regional Revenue Agency (BAPENDA) of Kuantan Singingi Regency. This study uses a qualitative research method with a phenomenological approach with data collection methods using interviews, observation and documentation. The result of this study is that the process of forging e-income innovation on PBB-P2 taxes at the Regional Revenue Agency (BAPENDA) of Kuantan Singingi Regency has not been maximized, this is caused by the following inhibiting factors: network, immature data collection, lack of socialization and public awareness, evaluation unscalable and lack of human resources.Keywords: Innovation, Taxes, Income, Socialization, E-Revenue, Local Government.